FAKTOR-FAKTOR YANG MEMENGARUHI KESIAPSIAGAAN PERSONEL DALAM LATIHAN MILITER: SYSTEMATIC LITERATURE REVIEW - Gianina Sembiring; Herni Pujiati; Samto Hadi Isnanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Personnel readiness is a critical aspect of military organizations because it determines the ability of units to perform tasks rapidly, accurately, and effectively. This study aims to identify and synthesize the factors influencing personnel readiness in military training. The method used is a Systematic Literature Review based on the PRISMA 2020 framework. The literature was retrieved from the Scopus database using the advanced search feature with keywords related to personnel readiness, military readiness, combat readiness, cognitive readiness, operational readiness, military training, training exercise, and military exercise. The initial search identified 146 articles, which were then screened based on title relevance and research context. As a result, 37 articles were retained for further analysis. The synthesis shows that personnel readiness in military training is influenced by six main groups of factors: training factors, individual factors, leadership factors, organizational factors, psychological-cognitive factors, and training technology factors. The findings indicate that personnel readiness is multidimensional and is not solely determined by physical training or procedural mastery, but also by motivation, competence, leadership, organizational support, the ability to cope with pressure, and the use of technology in training. This study concludes that improving personnel readiness requires an integrated, realistic, adaptive, and operationally relevant training design.